2015
DOI: 10.4149/gpb_2014039
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, antioxidant properties and hepatoprotective effects of chamomile (Matricaria recutita L.) decoction extract against alcohol-induced oxidative stress in rat

Abstract: Abstract. The present study assessed the chemical composition, antioxidant properties, and hepatoprotective effects of subacute pre-treatment with chamomile (Matricaria recutita L.) decoction extract (CDE) against ethanol (EtOH)-induced oxidative stress in rats. The colorimetric analysis demonstrated that the CDE is rich in total polyphenols, total flavonoids and condensed tannins, and exhibited an important in vitro antioxidant activity. The use of LC/MS technique allowed us to identify 10 phenolic compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 61 publications
4
17
0
Order By: Relevance
“…The chemical composition, antioxidant properties, and hepatoprotective effects of subacute pre-treatment with chamomile (Matricaria recutita L.) decoction extract (CDE) against ethanol (EtOH)-induced oxidative stress in rats was assessed, and it was suggested that CDE exerted a potential hepatoprotective effect against EtOH-induced oxidative stress in rats, at least in part, by negatively regulating Fenton reaction components such as H(2)O(2) and free iron, which are known to lead to cytotoxicity mediated by intracellular calcium deregulation ( 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…The chemical composition, antioxidant properties, and hepatoprotective effects of subacute pre-treatment with chamomile (Matricaria recutita L.) decoction extract (CDE) against ethanol (EtOH)-induced oxidative stress in rats was assessed, and it was suggested that CDE exerted a potential hepatoprotective effect against EtOH-induced oxidative stress in rats, at least in part, by negatively regulating Fenton reaction components such as H(2)O(2) and free iron, which are known to lead to cytotoxicity mediated by intracellular calcium deregulation ( 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to the study done in our laboratory, phytochemical studies of CDE revealed the presence of high concentrations of total polyphenols, total flavonoids, and condensed tannins. The use of HPLC-PDA-MS allowed to the identification of gallic acid, protocatechuic acid, chlorogenic acid, cafeic acid, cafeoylquinic acid, salicylic acid, quercetin, quinic acid derivative, hydroxybenzoic acid-O-hexoside, 5,7,4’-Trihydroxy-6,3’-dimethoxyflavone [ 52 ]. These molecules are the primal source of antioxidant ability of this plant that act as scavengers of free radicals [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, phytochemical analysis also revealed an important amount of tannins in the myrtle berries seeds aqueous extract containing 26.25 ± 01.27 mg TAE/g DM and 4.49 ± 0.27 mgCE/g DM respectively for total and condensed tannins. However, MBSAE tannins contents appear higher than those of other medicinal plants such as Matricaria recutita , Punica granatum and Securidaca longepedunculata . Indeed, besides their antioxidant activity, these molecules are implicated in the regulation of intestinal hypersecretion .…”
Section: Discussionmentioning
confidence: 94%